2013
DOI: 10.1088/0004-637x/776/2/100
|View full text |Cite
|
Sign up to set email alerts
|

THE LOCAL ENVIRONMENT OF ULTRALUMINOUS X-RAY SOURCES VIEWED BYXMM-NEWTON's OPTICAL MONITOR

Abstract: We have used XMM-Newton's Optical Monitor (OM) images to study the local environment of a sample of 27 Ultraluminous X-ray Sources (ULXs) in nearby galaxies. UVW1 fluxes were extracted from 100 pc regions centered on the ULX positions. We find that at least 4 ULXs (out of 10 published) have spectral types that are consistent with previous literature values. In addition the colors are similar to those of young stars. For the highest-luminosity ULXs, the UVW1 fluxes may have an important contribution from the ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 118 publications
(120 reference statements)
1
12
0
Order By: Relevance
“…We chose the ULXs because they are mostly associated with star forming regions and/or young SCs (e.g. Zezas et al 2002;Kaaret et al 2004;Berghea 2009;Mapelli et al 2010;Poutanen et al 2013;Berghea et al 2013), because they ) and because they have an estimated luminosity (assuming isotropy) higher than the Eddington luminosity of a 10 M ⊙ BH. For the high luminosity and for the anti-correlation with metallicity, Mapelli et al (2009) proposed that (a fraction of) ULXs are associated with MSBHs (see also Zampieri & Roberts 2009;Mapelli et al 2010;Mapelli et al 2011a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose the ULXs because they are mostly associated with star forming regions and/or young SCs (e.g. Zezas et al 2002;Kaaret et al 2004;Berghea 2009;Mapelli et al 2010;Poutanen et al 2013;Berghea et al 2013), because they ) and because they have an estimated luminosity (assuming isotropy) higher than the Eddington luminosity of a 10 M ⊙ BH. For the high luminosity and for the anti-correlation with metallicity, Mapelli et al (2009) proposed that (a fraction of) ULXs are associated with MSBHs (see also Zampieri & Roberts 2009;Mapelli et al 2010;Mapelli et al 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that the dynamics of the parent SC enhances the formation of bright X-ray binaries. In addition, a significant fraction of these bright X-ray sources are found to be slightly displaced (by few tens to hundreds of parsecs) from the closest young SC (Zezas et al 2002;Kaaret et al 2004;Berghea 2009;Rangelov et al 2012;Poutanen et al 2013;Berghea et al 2013). This has been interpreted as a consequence of natal kicks (e.g.…”
Section: Inaf-osservatoriomentioning
confidence: 99%
See 1 more Smart Citation
“…If this "extragalactic H II region" was formed by a compression of gas in the bridge, it would only have had 10-20 Myr to form. However, this is feasible, since Berghea et al (2013) have shown that the ages of typical massive star clusters associated with ULXs are typically 10 Myr old. A more detailed study of the correlation between the position of Taffy B1 and the host molecular cloud and associated star-formation would be worthwhile.…”
Section: The Compact Sourcesmentioning
confidence: 99%
“…Since mergers of BH binaries are among the most important sources of gravitational waves, the dynamical fate of BHs in star clusters strongly affects the predictions of the detection-rate by ground-based gravitational waves detectors (O'Leary et al 2006;Sadowski et al 2008;Downing et al 2010Downing et al , 2011Ziosi et al 2014;Morscher et al 2015;Rodriguez et al 2015;Chatterjee et al 2016;O'Leary et al 2016). Similarly, the dynamics of stellar remnants affects the demographics of X-ray binaries (Mapelli et al 2011;Downing et al 2011;Berghea et al 2013;Mapelli & Zampieri 2014;Goswami et al 2014). If equipartition is not reached, there might be relevant implications for the current local mass function of star clusters (e.g.…”
Section: Introductionmentioning
confidence: 99%